Pomegranate-like ZnxCd1-xS@MoS2 nano-heterostructure as a stable and efficient photocatalyst for H2 evolution. (February 2022) - Yin, Xing-Liang; Li, Lei-Lei; Lu, Yao; Han, Shu-Rui; Dou, Jian-Min; Li, Da-Cheng
Abstract: A novel pomegranate-like Znx Cd1-x S@MoS2 core@shell nano-heterostructure was synthesized by using a facile one-pot solvothermal approach. In this architecture, the MoS2 nanosheet and well-dispersed Znx Cd1-x S nanospheres serve as peel and seeds, respectively. While maintaining the advantages of nanoscale materials, such as high ratio of surface to volume and a relatively short charge transportation path, this unique structure also provides some additional positive features for H2 generation application: (1) the intimate contact of MoS2 and Znx Cd1-x S contributes to the well-defined heterostructure formation and thus enhances H2 generation efficiency; (2) the MoS2 nanosheets with amorphous-like structures providing numerous active sites for H2 generation; (3) the multiple pore nano structure promotes mass transfer and allows the active site through exposure; (4) the coated MoS2 with superior chemical stability protects Znx Cd1-x S from photocorrosion and disaggregation. With those advantages, the Znx Cd1-x S@MoS2 heterostructure exhibits a high photocatalytic H2 evolution rate of 28.22 mmol g −1  h −1 far exceeding that of pristine Znx Cd1-x S by a factor of more than 56 and maintains long term stability with no obvious active deterioration in 24 h performance evaluation. Moreover, the one-pot synthesis of this heterostructure significantly saves time and energy, rendering it cost-efficiency. The demonstrated strategy here could have great significance in the design and fabrication of the low-cost and high-efficient heterogeneous photocatalysts. Graphical abstract: Image 1 Highlights: The pomegranate-like Zn0.5 Cd0.5 S@MoS2 was synthesized via a one-pot approach. The activity of Zn0.5 Cd0.5 S@MoS2 is 56 times higher than that of pristine Zn0.5 Cd0.5 S. The Zn0.5 Cd0.5 S@MoS2 exhibits superior stability. The photocatalytic mechanisms were detailedly investigated.